Using Picture as a Media to Improve Students’ Skill in Writing Descriptive Text - Samira, Samira (Maspul Journal of English Studies, 2022)
The objective of this research was to know whether using picture as a media can improve students’ skill in writing descriptive text. The researcher used experimental research design. The sample of this research was chosen using random sampling, class VIII D as an experimental class and VIII B as a control class. The instrument of this research was pretest and post-test writing text especially descriptive text. This research has conducted at the second year of SMPN 2 Enrekang on May to June 2019. The data of this result showed that there was a significant improve between experimental class and control class. In experimental class the writing skill of students was improved which was in the experimental class there was treatment has given, using picture as media. While in control class there was no significant improve of students’ skill in writing descriptive text, which was in control class also there was treatment has given, the treatment was conventional method. The improvement can be proven by the Post-test Mean score between Experimental and control class 77.15 ˃ 67.74. Thus, it can be concluded that the use of picture can improve students’ skill in writing descriptive text.